Предмет: Алгебра,
автор: танюшка150399
Решите уравнение
(x-2)(x-3)(x-4)=(x-2)(x-3)(x-5)
Ответы
Автор ответа:
0
(x-2)(x-3)(x-4)=(x-2)(x-3)(x-5)
(x-2)(x-3)(x-4)-(x-2)(x-3)(x-5) =0
((x-2)(x-3))((x-4)-(x-5))=0
((x-2)(x-3))(x-4-x-5)=0
-9(x-2)(x-3)=0
x-2=0
x-3=0
x=2
x=3
(x-2)(x-3)(x-4)-(x-2)(x-3)(x-5) =0
((x-2)(x-3))((x-4)-(x-5))=0
((x-2)(x-3))(x-4-x-5)=0
-9(x-2)(x-3)=0
x-2=0
x-3=0
x=2
x=3
Похожие вопросы
Предмет: Английский язык,
автор: missnatasha20
Предмет: Английский язык,
автор: katena9487
Предмет: Русский язык,
автор: кирилл1746
Предмет: Математика,
автор: vladbuvin2000
Предмет: История,
автор: ruslan62541